ANALISIS KURIKULUM MERDEKA PADA MATA PELAJARAN FIQIH - Muh Al Ghifari; Wasith Achadi (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2024)
The current curriculum changes, namely the implementation of the independent curriculum, have a positive or negative impact on the performance of teachers and students at school. The aim of this research is to analyze the Independent Curriculum in Class 7/VII Fiqh Subjects at the Mts N 3 Sleman Yogyakarta School. This type of research is a case study using methods, namely: interviews, observation and documentation, and also literature study. The results of this research show that Fiqh subject teachers have implemented independent curriculum programs well because they are in accordance with the curriculum used by the school. The obstacles faced by teachers lie in the incomplete facilities and infrastructure for carrying out optimal learning processes.